A rare case report of neuro-brucellosis with concurrence of depression, visual impairment, bilateral sensorineural hearing loss, and paraplegia. - Hossein Pourmontaseri; Maziyar Rismani; Barbad Karami; Zahra Montaseri; Ali Azmi; Sedighe Hooshmandi (PLoS Neglected Tropical Diseases)
Neurobrucellosis is a rare manifestation of brucella infection, which would be life-threatening and result in multiple disabilities. Brucellosis commonly manifests with fever, arthralgia, and myalgia. Moreover, most patients with Neurobrucellosis present with significant lesions in the brain, spinal cord, or vertebral column; some cases show no lesions in their magnetic resonance imaging (MRI). The present case is a 32-year-old rural man with suspicious contact with animals at his work who was presented with ataxia, paraplegia, and urine-fecal incontinence without typical symptoms of brucellosis. Broad-spectrum diagnostic methods for neurobrucellosis were employed, including the Wright and 2-mercaptoethanol (2-ME) tests on plasma and brain, as well as spinal MRI. However, no significant pathologies were found in the brain or spinal imaging that could explain the patient's clinical condition, and the Wright and 2-ME tests were negative. Also, despite a comprehensive approach to different viral, bacterial, autoimmune, systemic, metabolic, and organic etiologies, the symptoms of the patient got worse, and he experienced depression, sensorineural hearing loss (SNHL), and visual impairment in the following months. Eventually, the patient's cerebrospinal fluid specimen Wright & 2-ME tests became positive, and a standard antibiotic regimen, including doxycycline, rifampin, and ceftriaxone, was administered for several months. In his last follow-up two years later, all neurological and psychological issues had disappeared except mild ataxia and hearing impairment. Hence, the prozone phenomenon should be considered in the false-negative Wright tests in endemic regions for brucellosis.